Teacher education in the teaching of text production at elementary school: a necessary transgression - de Oliveira, Andréa Ramos [UNESP]; Parisotto, Ana Luzia Videira [UNESP] (UNISINOS - Universidade do Vale do Rio Dos Sinos, 2023)
This article is based on a collaborative-critical action- research of an applied qualitative nature focusing on continued teacher education connected to the teaching of textual production. Its participants comprised teachers and school and system administrators. It aimed at assessing the teacher education model implemented by a city in the State of São Paulo by assessing its theoretical basis and appraising the outcomes of its instructional meetings. Data was collected by means of questionnaires answered by the participants and video footage recorded at the meetings. The collected data was categorized and analyzed based on the work of several researchers, such as Eraut (1987), Ferry (1987), Zeichner (1993), Demailly (1997), Pacheco and Flores (1999), Day (2001), Oliveira-Formosinho (2009), Cardoso et. al. (2012), Diniz-Pereira (2014), Shulman (2014), Carnin (2015), Guimarães (2016), and Ferreira and Santos (2016). As most participants resorted to textbooks and recommendations available on the Internet, it was necessary to promote their critical thinking about these sources. The instructional strategies employed enabled the participants to recognize the closeness between their class plans and the structures of the textbooks they consulted to plan their classes. The results suggest that promoting teacher’s authorship in class planning can assist in re-signifying the work they do.
A formação docente para o ensino da produção de texto na escola básica: uma transgressão necessária
Keywords: Teacher Education; Teaching of Mother Tongue; Textbook